Novel Genetic Variants of PPARγ2 Promoter in Gestational Diabetes Mellitus and its Molecular Regulation in Adipogenesis - Wu, Ling; Song, Yi; Zhang, Yuan; Liang, Bo; Deng, Yan; Tang, Tao; Ye, Yan Chou; Hou, Hong Ying; Wang, Chi Chiu (Frontiers in Endocrinology, 2021)
Peroxisome proliferator-activated receptor γ2 (PPARγ2) is a nuclear hormone receptor of ligand-dependent transcription factor with a key role in adipogenesis and insulin sensitization in diabetes mellitus. In this study, we investigated genetic variants in PPARγ2 promoter, its association with gestational diabetes mellitus (GDM), and its molecular regulation. PPARγ2 promoter and start codon (-2091 to +82 bp) from 400 pregnancies with GDM and 400 gestational-age matched control pregnancies were sequenced. Association and linkage disequilibrium of the identified polymorphisms with GDM was determined. ChIP-seq, gene silencing and dual-luciferase reporter assays were performed to confirm transcription factor binding sites and promoter activity of the variants. Transfection experiments were carried out to determine the effects of variants on gene expression and adipogenesis. Among 15 variants identified, 7 known variants were not significantly associated with the risk of GDM (odds ratio: 0.710-1.208, 95% confidence interval: 0.445-0.877 to 1.132-1.664, P > 0.05) while linkage disequilibrium was significant (D' > 0.7, R2 > 0.9). However, T-A-A-T-G haplotype was not significantly associated with GDM (χ2 = 2.461, P = 0.117). Five rare variants and 3 novel variants (rs948820149, rs1553638909 and rs1553638903) were only found in GDM. Transcription factor glucocorticoid receptor  (GR) bound to -807A/C (rs948820149) and knockdown of GR suppressed PPARγ2 promoter activity. This mutation significantly down-regulated PPARγ2 expression and alleviated adipogenesis. In conclusion, a novel -807A/C in PPARγ2 promoter was identified in Chinese women with GDM and the mutation affected GR binding and transcription of PPARγ2 for adipogenesis.